2021
DOI: 10.1042/bsr20202074
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in immune responses to SARS-CoV-2 in patients with COVID-19

Abstract: Millions of people infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) have been diagnosed with coronavirus infectious disease 2019 (COVID-19). The prevalence and severity of COVID-19 differ between sexes. To explain these differences, we analyzed clinical features and laboratory values in male and female COVID-19 patients. The present study included a cohort of 111 people, i.e. 36 COVID-19 patients, 54 sex- and age-matched common viral community-acquired pneumonia (CAP) patients, and 21 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…During SARS-CoV-2 infection, it has been reported that males present higher pro-inflammatory cytokine expression, including IL-6, than females (90,91). While COVID-19 is known to cause lymphopenia in both sexes, T cell frequencies and activation remains greater in females than males during SARS-CoV-2 infection, even at older ages (91,92). In contrast, male sex is associated with greater anti SARS-CoV-2 antibody production in convalescent patients (91,93,94) as well as fewer breakthrough SARS-CoV-2 infections following vaccination (95).…”
Section: Immunological Differences Between the Sexesmentioning
confidence: 99%
“…During SARS-CoV-2 infection, it has been reported that males present higher pro-inflammatory cytokine expression, including IL-6, than females (90,91). While COVID-19 is known to cause lymphopenia in both sexes, T cell frequencies and activation remains greater in females than males during SARS-CoV-2 infection, even at older ages (91,92). In contrast, male sex is associated with greater anti SARS-CoV-2 antibody production in convalescent patients (91,93,94) as well as fewer breakthrough SARS-CoV-2 infections following vaccination (95).…”
Section: Immunological Differences Between the Sexesmentioning
confidence: 99%
“…Also, the selected samples were obtained from various time points (7-35 days) after the positive RT-PCR test to account for variability and delay of elicited immune response among different individuals. Further, other studies have shown that male individuals produce weaker immune responses, particularly nAbs, than females [54,55]. Hence, identifying the thresholds of protective immunity in male individuals is essential to avoid false-negative results and accurately estimate herd immunity.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of the mean difference in lymphocyte counts at admission between patients with good and with poor COVID-19 outcomes has shown that lymphopenia was significantly associated with severe COVID-19 and this association was affected by age but not by sex (Zhao Q. et al, 2020). However, some studies have suggested that the male sex is inversely associated with lymphocyte count, especially in patients with comorbidity , although not always confirmed (Zhao G. et al, 2021). In the peripheral blood of SARS-CoV-2-infected patients, both CD4+ and CD8+ T cell blood counts are dramatically decreased compared to healthy controls, with the highest evidence observed in severe cases (de Candia et al, 2021).…”
Section: Acquired Immunity: T Cellsmentioning
confidence: 99%
“…In the peripheral blood of SARS-CoV-2-infected patients, both CD4+ and CD8+ T cell blood counts are dramatically decreased compared to healthy controls, with the highest evidence observed in severe cases ( de Candia et al, 2021 ). Nevertheless, male COVID-19 patients have shown lower CD4+ T cell and higher CD8+ T cell proportions than female patients, indicating a possible more severe immune dysregulation ( Zhao G. et al, 2021 ; Table 4 ).…”
Section: Acquired Immunity: T Cellsmentioning
confidence: 99%